Validation and psychometric properties of the drug users' quality of life scale in Iranian population - Sousan Heydarpour; Amir Jalali; Fatemeh Baghaei; Nader Salari (BMC, 2020)
Abstract Introduction Drug dependence and the resultant problems notably decrease the quality of life (QOL). Measuring the QOL in persons who use drugs (PWUDs) and planning to improve it can be helpful for rehabilitation programs. Given the absence of a standard tool to measure the quality of life of PWUD, the present study is an attempt to validate psychometric and cultural characteristics of non-injection drug users' QOL scale. Method The study was carried out as a validation and methodological work. The study population consisted of 273 PWUDs in Kermanshah-based drug clinics including outgoing and hospitalized patients. The participants were selected through convenient-quota sampling. After securing the required permission from the copyright owner of the tool, it was forward/backward translated. Face validity and content validity were determined quantitatively and qualitatively. To examine construct validity of the tool, explorative factor analysis and confirmatory factor analysis were used. Internal consistency was measured using Cronbach's alpha and statistical analyses were performed using SPSS (v.25) and LISREL (v.8). Results Explorative factor analysis (EFA) and confirmatory factor analysis (CFA) results supported the tool with one factor and 22 items. The R2 index in the model was equal to 0.99, which means that 99% of the variation of dependent variable (total score of QOL) is attributed to independent variable (22 statements). In other words, 99% of the variation of dependent variable is due to the independent variables in the model. The main indices of the model based on CFA all were higher than 0.9, which indicates goodness of fit of the model (χ2/DF = 2.18, CFI, NFI, TLI = 0.93 GF = 0.84, REMSEA = 0.066, R2 = 0.99). The correlative coefficient was significant (p < 0.05). The reliability of the tool based on internal consistency (Cronbach's alpha) for the subscales ranged from 0.84 to 0.85 and equal to 0.84 for the whole tool. Conclusion The Farsi version of non-injection drug users' QOL scale had acceptable indices and it was applicable to assess QOL in the target population. The tool can be used in different fields of drug addiction.